Analysis of Hospital Health Service Quality Towards Patient Loyal-ty Through Leadership Style at Tgk. Chik Ditiro Sigli Regional General Hospital - Rakhmat Akbar Dinur; Ermi Girsang; Fioni Fioni (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
This study examines the relationship between Hospital Healthcare Service Quality (HCSQ) and patient loyalty at Tgk. Chik Ditiro Sigli Regional General Hospital, with a focus on the mediating role of patient satisfaction and the influence of leadership styles. Employing a qualitative approach, data were collected through in-depth interviews, focus group discussions, and document analysis to capture the perspectives of patients, healthcare professionals, and hospital administrators. The findings reveal that key dimensions of HCSQ—such as responsiveness, empathy, communication, and facility environment—significantly impact patient satisfaction, which in turn mediates patient loyalty. Leadership styles emphasizing collaboration, communication, and patient-centeredness were found to enhance service quality and foster stronger patient-hospital relationships. Conversely, authoritarian leadership styles or those lacking effective communication negatively affected both employee performance and patient perceptions. The study highlights the importance of empowering employees, fostering teamwork, investing in infrastructure, and prioritizing patient-centered care to improve service quality and loyalty. These findings provide actionable insights for hospital management to enhance organizational performance and build long-term trust with patients. Future research is recommended to explore these relationships quantitatively across diverse healthcare settings and examine the role of cultural factors in shaping patient expectations and loyalty behaviors.